Diagnosis of the treatment of natural hazards in the Spanish school curriculum (Papeles, 2026)
Introduction: The cut-off low of October 29, 2024, in Valencia (Spain) has highlighted the urgent need to raise awareness and educate the population, especially school students, on natural hazards. In this context, it is essential to review the school curriculum to ensure an education that prepares new generations to face the challenges arising from climate change. Methodology: This study analyzes the content related to natural hazards is addressed in the official Spanish curricula (Early Childhood Education, Primary Education, Compulsory Secondary Education, and Baccalaureate), based on the Royal Decrees in force since 2022. The objective is to identify which content is included, which Specific Competencies (SC) are addressed, and what pedagogical approach is applied (descriptive, preventive, or critical). Results and discussion: The results show a limited presence of these contents, especially in the early stages, and at times fragmented, with a predominance of descriptive approaches and little orientation toward prevention and critical reflection. Conclusion: The study concludes that education on natural hazards must be transversal, situated, and transformative, and that existing gaps and overlaps offer opportunities to strengthen territorial literacy and student resilience.
Keywords: Natural hazards; school curriculum; ecosocial education; resilience; Spain